Prospek Industri Garam Tradisional Ditinjau Dari Aspek Teknis, Aspek Finansial Dan Aspek Pasar Di Kabupaten Aceh Besar - Marzuki Marzuki; Indra Indra; Sofyan Sofyan (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
ABSTRACT. This study aims to determine whether the traditional salt industry already has the appropriate standard manufacture the technical aspects and prospects of development of the traditional salt industry reviewed of the financial aspects of feasibility and prospects of the market aspects Opportunities for the salt industry in Aceh Besar district is still wide open. These results indicate that the average farmer owned land measuring 468 M2. Salt processing is still done traditionally, wiyh an average production of 25 kg of salt per day. Financial analysis explains that the salt production is feasible, with the B/C ratio of 1.48. IRR of 37.60 percent, means that manufacture salt is able to produce a greater opportunity cost than the cost of capital so that the desired feasible. With NPV of Rp. 5,515,758 per year and a payback period of 11 months for 2 years. Opportunities for the salt industry in Aceh Besar district is still wide open. Until 2014, Aceh Besar can only produce as much as 117.74 tons of salt people or 117 740 kg per year. While the number of requests to salt over 572 835 kg per year.